Optimized synthesis of luminescent silica nanoparticles by a direct micelle-assisted method. Issue 9 (23rd April 2019) - Del Secco, Benedetta; Ravotto, Luca; Esipova, Tatiana V.; Vinogradov, Sergei A.; Genovese, Damiano; Zaccheroni, Nelsi; Rampazzo, Enrico; Prodi, Luca
Abstract : Small PEGylated silica nanoparticles are synthesized in the presence of high concentrations of organic solvents. This method allows for the efficient incorporation of dyes with poor solubility in water, yielding bright silica nanoparticles. Abstract : Silica nanoparticles (NPs) are versatile nanomaterials, which are safe with respect to biomedical applications, and therefore are highly investigated. The advantages of NPs include their ease of preparation, inexpensive starting materials and the possibility of functionalization or loading with various doping agents. However, the solubility of the doping agent(s) imposes constraints on the choice of the reaction system and hence limits the range of molecules that can be included in the interior of NPs. To overcome this problem, herein, we improved the current state of the art synthetic strategy based on Pluronic F127 by enabling the synthesis in the presence of large amounts of organic solvents. The new method enables the preparation of nanoparticles doped with large amounts of water-insoluble doping agents. To illustrate the applicability of the technology, we successfully incorporated a range of phosphorescent metalloporphyrins into the interior of NPs. The resulting phosphorescent nanoparticles may exhibit potential for biological oxygen sensing.